Flow cytometry applications for the analysis of chemokine receptor expression and function. Issue 4 (24th January 2014) - Anselmo, Achille; Mazzon, Cristina; Borroni, Elena Monica; Bonecchi, Raffaella; Graham, Gerard J.; Locati, Massimo
Abstract Chemokine receptors play an important role in leukocyte migration, both in physiological and pathological conditions, and the interest in new methodologies for their detection is increasing. In this review, we focused on chemokine receptors detection through flow cytometric approaches, including the use of specific antibodies and fluorescent chemokines, and on approaches aimed at the analysis of their functions, from intracellular trafficking to signaling activities. © 2014 International Society for Advancement of Cytometry